O Brasil e a Companhia do Alto Douro : (1756-1825) - Sousa, Fernando de (2008)
In this work we deal with the relations between the Company and Brazil, between 1756 – the year of its foundation – and 1825, the year when the diplomatic relations with Brazil were normalized. Among the privileges granted to the Company, we highlight the monopoly of the exclusive commerce of all the wines, brandies and vinegars exported from Porto to the captainships of São Paulo, Rio de Janeiro, Bahia and Pernambuco, a trade that until 1755-1756 was dominated by the English but that with the creation of the Royal Oporto Wine Company, among other reasons, will get to the hands of the Portuguese high-bourgeoisie. Brazil quickly became an important market for the exportation of the wines of the Upper Douro, the most important branch of the Company’s businesses during the two first decades of its existence but not, contrary to the opinion of some historians, the most lucrative sector of the activity developed by that Institution.